La forêt, un patrimoine au prisme de l’écologisation : le cas des Landes de Gascogne - Clarisse Cazals; Philippe Deuffic; Arnaud Sergent; Ludovic Ginelli (VertigO)
In a context of sustainable development, which stresses the importance of the ecological aspect of forest issues, the process of definition and legitimization of forest heritage has changed. This article deals with an interdisciplinary approach of the different forms of social construction of forest heritage by studying the relationships between forest actors which are faced with the global dynamic of ecologization. In particular, this analytical grid is mobilized to interpret the contemporary evolution of the Landes de Gascogne’s forest heritage through the ecologization of both the forest property and the wood based industry.